2017
DOI: 10.24188/recia.v9.n2.2017.552
|View full text |Cite
|
Sign up to set email alerts
|

Dinámica del fósforo en un agroecosistema conservacionista maíz-ganado de sabanas neotropicales

Abstract: Phosphorus is one of the limiting elements in acid soils, so the incorporation of strategies for its cycling within an agroecosystem is one of the key variables, in order to optimize agricultural production. The dynamics of phosphorus in a maize-livestock agroecosystem were evaluated under the types of forages introduced: Brachiaria dyctioneura (Bd), a grass and Centrosema macrocarpum (Cm), a legume, which in turn served as associated perennial coverages maize grown with direct sowing. The dynamics of this ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The highest P contents were observed in Pa in 1984, while the lowest were found in RC and AC of the same year (Table 3). The P value in Pa is consistent with reports on pasture soil by Burst et al (2020) and can be attributed to the application of P mineral fertilizers (Alabi et al, 2019) and to grazing residues (cattle manure and urine) that increase the availability of P in the soil (Ramírez-Iglesias et al, 2017).…”
Section: Cambisol Quality By Agricultural Use Timesupporting
confidence: 88%
See 1 more Smart Citation
“…The highest P contents were observed in Pa in 1984, while the lowest were found in RC and AC of the same year (Table 3). The P value in Pa is consistent with reports on pasture soil by Burst et al (2020) and can be attributed to the application of P mineral fertilizers (Alabi et al, 2019) and to grazing residues (cattle manure and urine) that increase the availability of P in the soil (Ramírez-Iglesias et al, 2017).…”
Section: Cambisol Quality By Agricultural Use Timesupporting
confidence: 88%
“…This is confirmed by the varied-aged rocks where the CM of the RR develops, such as Holocene alluvium, Miocene detrital sediments, and Eocene limestones and marls (Salgado-García et al, 2017). The properties that did not show significant differences between the factors of use and establishment year were the following: a) pH, with a prevalence of neutral over moderately acidic (7.3 to 6.1) (SEMARNAT, 2002); acidic pHs in agricultural soils are due to intensive farming and the continuous use of acid-forming inorganic fertilizers (Mulat et al, 2021); b) EC showed low values, characteristic of CM (Salgado-García et al, 2017); this property helps crops assimilate other soil nutrients better (Navarro-García and Navarro-García, 2013); c) N presented low values -especially in RC and AC-, closely related to low to medium OM values, which reduces the mineralization level of N (Alabi et al, 2019); d) P showed high values due to cattle excreta and applied fertilizers (Ramírez-Iglesias et al, 2017); e) BD was higher in Pa, associated with compaction as a result of extensive livestock farming (Xu et al, 2021); and f) AS had a low WMD in RC and Pa, which indicates a structural stability loss, while the increase in AC is related to the OM content; when attached to soil mineral particles, they form clay-metal-humic bonds that increase structural stability (De Freitas et al, 2018).…”
Section: Results and Discussion Cambisol Quality Between Agricultural...mentioning
confidence: 99%
“…VIERA et al (2019) argue that the species and their vegetation composition can have a considerable effect on the accumulation of organic matter (OM) in the soil, favoring decomposition via microbial communities, while this activity is limited in the dry season. RAMÍREZ-IGLESIAS et al (2017a) claim that increased production of GLB can mean an alternative for livestock in the dry season. Despite intensive grazing in pastures, there is still a quantity of green plant material after that process that can be consumed by livestock.…”
Section: Resultsmentioning
confidence: 99%